Social norm coordination and readiness to change female genital cutting: Evidence from Senegambia - K. Wander; B. Shell-Duncan (Elsevier, 2020)
Background: Female genital cutting (FGC), which poses risks to the health of girls, has proved remarkably persistent in many communities in Africa, despite decades of efforts to discourage it. The social coordination norm model of FGC attributes this persistence to high social costs for uncut women, such as exclusion from marriage markets or social support networks. Objective/methods: To test the social coordination model of FGC decision-making in Senegambia, we examined variation in FGC across communities, attitudes toward FGC, and how attitudes affected readiness to change (abandon) FGC. We used an ethnographically-grounded survey to assess valuation of FGC and readiness to change FGC. We used factor analysis to identify constructs in valuation of FGC and logistic regression models to evaluate hypothesized predictors of cut status and readiness to change FGC drawn from the social coordination norm model. Results: 1220 women with at least one daughter completed the survey; FGC valuation and readiness to change were characterized in 820 of these women. Findings were generally consistent with the social coordination norm hypothesis: Both locality and ethnicity were associated with cut status, and the prevalence of cutting across communities clustered at high and low levels. Factor analysis identified two distinct concerns in valuation of FGC-social advantages and health costs-and these were distributed differently for cut and uncut women, reflecting distinct normative schema. Further, readiness to change FGC differed in predicted ways with valuation of FGC. Conclusions: These findings support the social coordination norm model, and reveal distinct normative schema among cut and uncut women. Furthermore, our findings point to a dynamic reassessment of social benefits and health costs underlying FGC decision-making and readiness to change FGC. The reappraisal of social benefits may be an unrecognized opportunity for programs aiming to discourage FGC.